1997
DOI: 10.1093/humrep/12.1.132
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial perfusion across the normal human menstrual cycle assessed by laser Doppler fluxmetry

Abstract: This study investigated variations in microvascular perfusion of human endometrium across the menstrual cycle, using a laser Doppler technique to assess red blood cell (RBC) flux. Endometrial RBC flux was monitored by laser Doppler fluxmetry via a fibre optic probe inserted transvaginally into the uteri of 19 conscious normal volunteer women, on four occasions at weekly intervals over one menstrual cycle. Regional variation in RBC flux was investigated in 16 surgical patients under general anaesthesia and in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
2
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 11 publications
2
24
2
3
Order By: Relevance
“…Steer et al (115) reported that the chance of pregnancy was maximal when the uterine pulsatility index (PI) was in the range of 2.00 to 2.99. Subsequently, Gannon et al (116) used an intrauterine laser Doppler technique to measure endometrial microvascular blood flow, which varied throughout the menstrual cycle, with increases in blood flow during the early follicular and early luteal phases.…”
Section: Endometrial Blood Flowmentioning
confidence: 99%
“…Steer et al (115) reported that the chance of pregnancy was maximal when the uterine pulsatility index (PI) was in the range of 2.00 to 2.99. Subsequently, Gannon et al (116) used an intrauterine laser Doppler technique to measure endometrial microvascular blood flow, which varied throughout the menstrual cycle, with increases in blood flow during the early follicular and early luteal phases.…”
Section: Endometrial Blood Flowmentioning
confidence: 99%
“…Peri-menstruation, no significant changes in blood flow were observed and no ischaemia/reperfusion episodes have been detected (Fraser & Peek 1992). Only very low levels of hypoxia-inducible factor 1 a (HIF1A) and HIF2A, early markers of hypoxia, have been observed in the human endometrium (Gannon et al 1997). An alternative theory to vasoconstriction and hypoxia suggests that menstruation is an inflammatorytype process (Salamonsen 2003).…”
Section: Vascular Endothelial Growth Factor-amentioning
confidence: 99%
“…Overall blood flow in the endometrium was not significantly reduced peri-menstrually [87] and no endometrial ischaemia/reperfusion episodes have been detected peri-menstrually by a Doppler technique [88]. In addition, only very low levels of the early markers of hypoxia HIF-1a and HIF-2a have been observed in the human endometrium [89].…”
Section: Role Of Vegf In Endometrial Angiogenesismentioning
confidence: 99%